Pengelolaan Sampah Dengan Pola 3 R Untuk Memperoleh Manfaat Ekonomi Bagi Masyarakat - Setianingrum, Reni Budi (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2018)
The purpose of this community service program are to change the previous paradigm of local people who assumed that waste is a useless material, to a new paradigm which believed that waste can be potential a raw material for handicraft that have economic value, provide skill through training to make handicraft made from plastic waste and change the old pattern of collect-transport-throw away, into 3R patterns, ie reduce, reuse and recycle and also establish a waste management group. The method of this community service program was implemented in 3 (three) stages, Firstly counseling in improving environmental awareness. Secondly, training how to recycle plastic crackle and sachet, and thirdly, assisting garbage management group. The result of this service program areÂ  that there is a change of paradigm of the service programâ€™s partners who previously throw garbage carelessly, recently they are already have awareness of sorting the waste between non recyclable and recyclable, citizens also have the skills to produce handicrafts made from the raw materials of plastic waste. In addition, there is existing group which is expected to be the future â€œBank Sampahâ€.Â Keywords = waste, recycle, plastic waste.